HUBUNGAN BEBAN KERJA DENGAN STRESS KERJA PADA PERAWAT DI RUANG INTENSIVE CARE DI RSUD LABUANG BAJI MAKASSAR - Al Frida (Stikes Graha Edukasi Makassar, 2018)
Research Objectives: The purpose of this study to look at the relationship workload with work stress nurses in intensive care room. Method: In this study using the research design used in this study is an analytical survey of a study where variables that include relationships and variables that include effects observed at the same time. The sample size in this study 34 respondents who match the inclusion criteria. The data were collected by using questionnaires. Result: The result of the research shows that there are enough workload of 61,8% of respondents, and 38,2% of respondents with less work load. And stress work as much as 55,9% respondents who stress enough work, and as many as 15 (44,1%) respondents who stress less work. And there is a working load relation with work load work (p = 0,020). Discussion: Workload is the body's ability to work in the job. From the point of view, the ergonomics of each workload received must be appropriate and balanced to the physical and psychological ability of workers who receive the work load. Suggestion: The results of this study can give attention and proper problem solving to nurses who show symptoms of work stress